ETIKA PELAYANAN PUBLIK DI KANTOR KECAMATAN RUMBIA KABUPATEN JENEPONTO. - Nurfadillah, Nurfadillah; Usman, Jaelan; Yusuf, Muh (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the ethics of public service at the Rumbia District Office, Jeneponto Regency. The type of research used is a qualitative method. Data collection was carried out using observation, interview and documentation techniques. The results of the research show that the public service ethics implemented in the Rumbia District Office, Jeneponto Regency have not been fully implemented in accordance with applicable procedures or operational standards (SOP) when viewed from the aspect of 1) Equality of Rights, equality of rights has been running well, serving the community without looking at social, religious, political and class status between rich and poor, 2) Justice, serving the community in a friendly manner, providing explanations to people who want to carry out the administrative process, all communities are treated equally in the sense that whoever comes first is the one who served, 3) Loyalty of employees, especially employees with honorary status who are still loyal to the agency even though they have worked for years with salaries that are not that large, 4) Accountability has not been fully carried out properly.